2018
DOI: 10.1108/jamr-12-2017-0124
|View full text |Cite
|
Sign up to set email alerts
|

Phase-wise analysis of dynamic relationship among gold, crude oil, US dollar and stock market

Abstract: Purpose The purpose of this paper is to investigate the dynamic relationship among Gold, Crude oil, Indian Rupee-US Dollar and Stock market-Sensex (gold, oil, dollar and stock market (GODS)) in the pre-crisis, the crisis and the post-crisis periods in the Indian context. Design/methodology/approach The authors use Johansen’s cointegration technique, Vector Error Correction Model (VECM), Vector Auto Regression, VEC Granger Causality/Block Exogeneity Wald Test, and Granger Causality and Toda Yamamoto modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(28 reference statements)
0
23
0
Order By: Relevance
“…The result is in line with the study by Stefan & Robiyanto (2019) about the negative correlation between the ASEAN stock market and the USD/IDR exchange rate. Similarly, the study by Živkov et al (2016) in Europe and the study by Singh & Sharma (2018) in India discovered negative correlation between stock market and exchange rate.…”
Section: May 2020mentioning
confidence: 69%
See 2 more Smart Citations
“…The result is in line with the study by Stefan & Robiyanto (2019) about the negative correlation between the ASEAN stock market and the USD/IDR exchange rate. Similarly, the study by Živkov et al (2016) in Europe and the study by Singh & Sharma (2018) in India discovered negative correlation between stock market and exchange rate.…”
Section: May 2020mentioning
confidence: 69%
“…Gold is one of the precious metals which is the most important commodity in the world that can attract investors' interest and trade internationally (Singh & Sharma, 2018). According to Natalie & Artigas (2010) gold has two roles as a hedging…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that oil prices are positively related stock markets of all ten net oil-importing countries and the fundamentals of the stock market also play a significant role in these dynamics. Singh and Sharma (2018) estimated the dynamic relationship between gold, crude oil, US dollar, exchange rate and Sensex and found a long-run relationship between crude oil and Sensex. Another study was conducted on GCC countries by (Yao et al, 2018) where the authors studied the lead-lag structure between the oil price and stock market.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Phan et al (2020) found strong evidence for a negative effect of crude oil price uncertainty on firm performance at both aggregate market and sectoral levels. Singh & Sharma (2018) present that during the crisis period, both crude oil and Sensex models show long-run causality, however, in some cases, results indicate short-run causality and there is one-way causality from USD and Sensex to crude oil, and from gold and Sensex to USD. Urom et al (2020) show a substantial level of business cycle spillover among the markets with crude oil.…”
Section: Literature Reviewmentioning
confidence: 79%